Morte e vida palestina: a reorientação tática do colonialismo israelense na Faixa de Gaza - Santos, Isabela Agostinelli dos (2023)
For the first time, in August 2005, the Israeli State withdrew its settlements from a Palestinian territory that had been under military occupation since 1967: the Gaza Strip. Since then, Israel claims it no longer has any responsibility for that space and its population, with the justification that there is no longer a military occupation in Gaza. However, far from “disengaging” from Gaza, Israel began to exercise a type of domination by remote control, in which infrastructure networks became the main mechanism of control over the life and death of Palestinians in the region. This domination is exercised not only through control over Gaza’s borders, but mainly through the implementation of “economic de-development” and policies of socio-spatial isolation. This thesis aims to analyze such policies in order to answer the following questions: how and why did the State of Israel reorient its tactics of colonial domination in Gaza? We argue that disengagement was a tactical reorientation of forms of colonial domination, which materializes in the functioning of mobility policies, control of economic infrastructure and resources. In this process, there is a fundamental articulation between colonial politics, understood in terms of ideology and grand strategy, whose objective is to conquer the greatest amount of land with the smallest number of natives possible, and the policies, understood in terms of tactics and public policies, which by its turn are informed by politics and give meaning to the project of Israeli settler colonisation of Palestine. A genealogy of the economic dedevelopment and socio-spatial isolation of the Gaza Strip reveals that, at least since the 1980s, it has become a major demographic threat to the establishment of an Israeli state with a Jewish majority. Disengagement would be a way to resolve this demographic equation, which was unfavorable to the Israelis, while maintaining control over the space, population, and resources of Gaza, now operating “remotely”. The impacts of implementing such policies are daily experienced by Gazans, who are unable to develop their own socioeconomic life in an environment where resources are scarce. Gazans are also constantly placed in a limbo between life and death, due to the infrastructural violence they face. In this scenario, life in Gaza, narrated by its own inhabitants, resembles more a “slow death” than a dignified life